Impact of Putative Probiotics on Growth, Behavior, and the Gut Microbiome of Farmed Arctic Char (Salvelinus alpinus) - Knobloch, Stephen; Skírnisdóttir, Sigurlaug; Dubois, Marianne; Kolypczuk, Laetitia; Leroi, Françoise; Leeper, Alexandra; Passerini, Delphine; Marteinsson, Viggó Þ. (Frontiers in Microbiology, 2022)
Beneficial bacteria promise to promote the health and productivity of farmed fish species. However, the impact on host physiology is largely strain-dependent and studies on Arctic char (Salvelinus alpinus), a commercially farmed salmonid species, are lacking. In this study, ten candidate probiotic strains were subjected to in vitro assays, small-scale growth trials and behavioural analysis with juvenile Arctic char to examine the impact of probiotic supplementation on fish growth, behaviour and the gut microbiome. Most strains showed high tolerance to gastric juice and fish bile acid, as well as high auto-aggregation activity, which are important probiotic characteristics. However, they neither markedly altered the core gut microbiome, which was dominated by three bacterial species, nor detectably colonised the gut environment after the 4-week probiotic treatment. Despite a lack of long-term colonisation, the presence of the bacterial strains showed either beneficial or detrimental effects on the host through growth rate enhancement or reduction, as well as changes in fish motility under confinement. This study offers insights into the effect of bacterial strains on a salmonid host and highlights three strains, Carnobacterium divergens V41, Pediococcus acidilactici ASG16 and Lactiplantibacillus plantarum ISCAR-07436, for future research into growth promotion of salmonid fish through probiotic supplementation.